Taṭbīq al-Imlā’ al-Manẓūr bi al-Kharīṭah aż-Żihniyyah Li Tarqiyah Qudrah aṭ-Ṭullāb Fī Tarkīb al-Jumal al-Mufīdah (Dirāsah Tajrībiyah Li al-Marḥalah al-`Āliyah Bi Ma`had Dār al-`Ulūm al-`Aṣrī Banda Aceh) - Isna Isna; Azman Ismail; Buhori Muslim (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
Imlak is the activity of changing sounds that can be understood into written symbols, but these letters are placed in the correct position of words, to correct the pronunciation and meaning desired. The title of this research is "The Implementation of ImlakMandhur through Mind Mapping in Increasing the Students’ Ability in Writing of Complete Sentences (The Experimental Study at Dayah Modern DarulUlum) ".There are some reasons for the researcher to conduct this research. Low motivation of students. The students were sleepy, when the teacher taught in the class.Some of them played to each other and did not pay attention to the lesson. When the teacher instructs them to write the mufradat,, they were unable to write properly and correctly, and some errors was found in writing mufradat. As for the difficulty of students in writing Arabic mufradat, they do not master the rules and the way in connecting Arabic letters. Besides they also lack of vocabulary in writing. The problems that dealing by the students, it caused by the monotonous method. The purpose of this study is to increase the students’ ability in Arabic writing by using ImlakMandhur Method through Mind Mapping. It aims to increase the students’ ability in writing. The population was all the students at Modern Darul Ulum, namely 933 students. The sample was 30 students at class X1c as the experimental group and 30 students at X1A as control group. The researcher used semi- experimental research design in conducting this research. Post test and observation was used to collect the data. The result was found that the implementation of ImlakMandhur by using Mind Mapping Media can increase the students’ ability in Arabic writing. In this case, the average score for the experimental group was higher than control group (87, 2 higher than 79.8). It means that the t-test was higher than (t table = 2, 04 from 5% from 1 %).